Low‐Power Optoelectronic Synaptic Transistors with Multimodal Neuromorphic Computation and Retinal‐Inspired Multiband Optical Binary Communication - Bo Huang; Linfeng Lan; Jiayi Pan; Fuzheng Qi; Jing Li; Churou Wang; Yaping Li; Dechun Zeng; Jiale Huang; Jintao Xu; Junbiao Peng (Small Science)
Biomimetic neuromorphic optoelectronics exude tempting attraction in multimodal interaction and visual applications because of their capability of integrating sensing, memorizing, and processing in a single device. Herein, a natural dextran film that is intrinsically green and transparent is employed as the dielectric of the optoelectronic synaptic transistors (OSTs). The resulting dextran‐OSTs that operate at an ultralow energy consumption (15.89 aJ) exhibit multimodal neuromorphic computation ability with excellent synaptic plasticity, including pair‐pulse facilitation (PPF, as high as 494%), spike voltage/frequency/duration/number‐dependent plasticity, and a high recognition accuracy of 89.95% by handwritten digital datasets. Furthermore, the device exhibits visual self‐adaptation ability and audiovisual fusion effect, showcasing the immense potential in self‐adaptation and synergy sensing. More importantly, the dextran‐OSTs can significantly advance the capabilities of binary optical information processing and memorizing. This demonstrates the great advantages of dextran‐OSTs in multimodal neuromorphic computation, visual self‐adaptation, synergy sensing, and multiband optical communication.